Galvanized steel sheet surface treatment solution, method for manufacturing galvanized steel sheet having surface treatment film, and galvanized steel sheet having surface treatment film

A surface treatment liquid for zinc-based steel plates, incorporating specific components and applied in defined proportions, addresses the challenge of maintaining corrosion resistance in environments with salt accumulation, while ensuring sweat resistance and storage stability.

JP2025040894AActive Publication Date: 2025-03-25JFE STEEL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023147973
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

Conventional zinc-based steel plates with surface-treated coatings exhibit excellent corrosion resistance in salt spray tests but fail to maintain this resistance in environments where salt accumulates, such as under eaves, due to differences in corrosion mechanisms.

Method used

A surface treatment liquid containing a resin compound with a bisphenol skeleton, a cationic urethane resin emulsion, a silane coupling agent, an organic titanium chelate compound, a tetravalent vanadium compound, a phosphoric acid compound, and water, applied in specific proportions to form a coating that provides excellent corrosion resistance and sweat resistance without using chromium compounds.

Benefits of technology

The surface treatment coating achieves excellent corrosion resistance on flat plates and processed parts, including environments where salt accumulates, while maintaining sweat resistance and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040894000001
    Figure 2025040894000001
  • Figure 2025040894000002
    Figure 2025040894000002
  • Figure 2025040894000003
    Figure 2025040894000003
Patent Text Reader

Abstract

To provide a surface treatment solution: capable of manufacturing a galvanized steel sheet having a surface treatment film and excellent in flat plate part corrosion resistance, processed part corrosion resistance, flat plate part corrosion resistance in environment in which salt accumulates and perspiration resistance; and excellent in storage stability.SOLUTION: A galvanized steel sheet surface treatment solution includes a resin compound having a specific bisphenol skeleton, cationic urethane resin emulsion having a specific cationic functional group, a silane coupling agent having a specific reactive functional group, an organic titanium chelate compound, a tetravalent vanadium compound, a phosphate compound and water at a specific proportion and has a pH of 5.5 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface treatment liquid for a zinc-based plated steel sheet, a method for producing a zinc-based plated steel sheet with a surface treatment film, and a zinc-based plated steel sheet with a surface treatment film. [Background technology]

[0002] Zinc-plated steel sheets are widely used in the fields of automobiles, home appliances, building materials, etc. To improve the corrosion resistance (white rust resistance, red rust resistance) of zinc-plated steel sheets, techniques have been proposed to form surface treatment films on the surfaces of zinc-plated steel sheets using inorganic compounds, organic compounds, organic polymer materials, or compositions combining these.

[0003] It has also been confirmed that when a person touches a zinc-based plated steel sheet directly, the part touched discolors over time. This is a phenomenon in which the surface of the zinc-based plated steel sheet discolors when the person's sweat, which is weakly acidic, adheres to the surface of the zinc-based plated steel sheet. If the color tone changes only in the part where the sweat adheres, the appearance of the surface of the zinc-based plated steel sheet becomes non-uniform, which is problematic. Therefore, the surface treatment film on the zinc-based plated steel sheet is required to have excellent sweat resistance, that is, to prevent the appearance of the surface of the zinc-based plated steel sheet from becoming non-uniform even when sweat adheres to it.

[0004] Patent Document 1 discloses a technology for forming a surface treatment film having excellent corrosion resistance by treating the surface of a zinc-based plated steel sheet with a surface treatment liquid containing a specific resin compound, a urethane resin emulsion having specific cationicity, a silane coupling agent having a specific functional group, a specific organic titanium chelate compound, a tetravalent vanadium compound, a molybdic acid compound, a fluorine compound, and water in specific ratios. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-67369 A Summary of the Invention [Problem to be solved by the invention]

[0006] The corrosion resistance of a zinc-based plated steel sheet having a conventional surface treatment film (surface-treated steel sheet) has generally been evaluated by a salt spray test (SST, JIS-Z-2371-2000) as described in Patent Document 1. However, the inventors have found that even a surface-treated steel sheet having excellent corrosion resistance in the SST may not exhibit excellent corrosion resistance when used in an environment where salt accumulates, such as under the eaves.

[0007] In a typical atmospheric corrosion environment, salt that has flown in adheres to the surface of the coated steel sheet, but the salt that has adhered to the surface of the coated steel sheet is washed away during rainfall. On the other hand, in an environment such as under an eaves, the rain does not fall on the surface of the coated steel sheet even during rainfall, so the salt accumulates without being washed away. Furthermore, environments such as under an eaves tend to have poor sunlight and tend to have long periods of wetness. Therefore, it is believed that the corrosion mechanism of coated steel sheets in environments such as under an eaves where salt accumulates is different from that of coated steel sheets in typical atmospheric corrosion environments, and there has been a demand for the design of coated steel sheets that can ensure corrosion resistance even in such environments.

[0008] In view of the above problems, the present invention aims to provide a surface treatment solution that is capable of producing a zinc-based plated steel sheet with a surface treatment film that does not contain chromium compounds and that is excellent in flat-plate corrosion resistance, processed-plate corrosion resistance, flat-plate corrosion resistance in an environment where salt accumulates, and sweat resistance, and that has excellent storage stability. Another aim of the present invention is to provide a method for producing a zinc-based plated steel sheet with a surface treatment film using the surface treatment solution, and a zinc-based plated steel sheet with a surface treatment film produced by the production method. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to solve the above problems, and have come to the following findings. In an environment where salt accumulates, it is important that the surface treatment film contains a component that can be dissolved from the surface treatment film when a water film is formed on the surface of the surface treatment film due to the moisture absorption action of salt, and that can form a compound that can exhibit barrier properties on the surface of a zinc-based plated steel sheet. Therefore, by making the surface treatment liquid contain a predetermined amount of a phosphate compound, it is possible to produce a surface treatment film that has excellent flat-plate corrosion resistance in an environment where salt accumulates. The present inventors have further discovered that by making the surface treatment liquid contain a predetermined amount of a phosphate compound, the sweat resistance of the surface treatment film is also improved.

[0010] That is, the gist and configuration of the present invention are as follows.

[0011] [1] A resin compound (A) having a bisphenol skeleton represented by the following general formula (I), a cationic urethane resin emulsion (B) having at least one cationic functional group selected from primary to tertiary amino groups and quaternary ammonium salt groups; a silane coupling agent (C) having at least one reactive functional group selected from an active hydrogen-containing amino group, an epoxy group, a mercapto group, and a methacryloxy group; an organic titanium chelate compound (D); A tetravalent vanadium compound (E), A phosphoric acid compound (F), Water (G) The surface treatment solution for zinc-based plated steel sheet contains the above in an amount that satisfies the following conditions (1) to (5) and has a pH of 5.5 or less. (1) The solid content mass of the resin compound (A) (A S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S ) the solid content mass (B S ) ratio [(B S ) / {(A S )+(B S)+(C S )}] is 0.10 or more (2) The solid content mass of the resin compound (A) (A S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S ) the solid content mass (C S ) ratio [(C S ) / {(A S )+(B S )+(C S )}] is 0.85 or less (3) The titanium-equivalent mass (D Ti ) the solid content mass (C S ) ratio {(C S ) / (D Ti )} is 50~70 (4) The titanium-equivalent mass (D Ti ) the vanadium-equivalent mass (E V ) ratio {(E V ) / (D Ti )} is 0.30 or more (5) The total solid mass of the surface treatment solution (T S ) the phosphorus equivalent mass (F P ) ratio {(F P ) / (T s )} is 0.015 to 0.400 [ka] In formula (I), Y1 and Y2 bonded to a benzene ring are each independently a hydrogen atom or a Z group represented by the following general formula (II) or (III), the average number of Z groups substituted per benzene ring is 0.2 to 1.0, and n represents an integer of 2 to 50. [ka] [ka] In formulas (II) and (III), R1, R2, R3, R4, and R5 each independently represent a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a hydroxyalkyl group having 1 to 10 carbon atoms; - represents a hydroxide ion or an acid ion.

[0012] [2] The surface treatment solution described in [1] above is applied to the surface of a zinc-based plated steel sheet, and then dried under conditions of a maximum sheet temperature of 40 to 180°C to obtain a coating weight of 0.2 g / m per side. 2 A method for producing a zinc-based plated steel sheet having a surface treatment film, comprising the above-described step of forming a surface treatment film.

[0013] [3] A zinc-based plated steel sheet having a surface treatment film, produced by the method for producing a zinc-based plated steel sheet having a surface treatment film according to [2] above. Effect of the Invention

[0014] The surface treatment solution of the present invention is capable of producing a zinc-based plated steel sheet with a surface treatment film that does not contain a chromium compound and is excellent in flat portion corrosion resistance, processed portion corrosion resistance, flat portion corrosion resistance in an environment where salt accumulates, and sweat resistance, and has excellent storage stability. The method of producing a zinc-based plated steel sheet with a surface treatment film of the present invention is capable of producing a zinc-based plated steel sheet with a surface treatment film having the above-mentioned excellent properties. The zinc-based plated steel sheet with a surface treatment film of the present invention has the above-mentioned excellent properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, embodiments of the surface treatment solution for zinc-based plated steel sheet, the method for producing a zinc-based plated steel sheet with a surface treatment film, and the zinc-based plated steel sheet with a surface treatment film according to the present invention will be described. Note that the embodiment described below is one example of the present invention, and the configuration of the present invention is not limited to this specific example.

[0016] [Zinc-plated steel sheet] In order to obtain the effect of the surface treatment solution according to one embodiment of the present invention, it is desirable to apply the surface treatment solution to a zinc-based plated steel sheet. The zinc-based plated steel sheet is composed of a base steel sheet and a zinc-based plating film, and is used for home appliances, building materials, automobile parts, and the like. As the zinc-based plated steel sheet, an electrolytic zinc-plated steel sheet, a hot-dip zinc-plated steel sheet, a zinc-aluminum alloy-plated steel sheet, a zinc-iron alloy-plated steel sheet, a zinc-magnesium alloy-plated steel sheet, a zinc-aluminum-magnesium alloy-plated steel sheet, and the like can be used. The surface treatment solution according to one embodiment of the present invention can also be applied to aluminum-based materials such as aluminum-plated steel sheet, aluminum-Si alloy-plated steel sheet, and aluminum sheet.

[0017] Furthermore, for the purpose of improving the blackening resistance of the zinc-based plated steel sheet, a trace amount of Ni or Co may be added to the zinc-based plating film, or these metals may be precipitated on the surface of the zinc-based plated steel sheet using an acidic or alkaline aqueous solution containing Ni, Co or Fe.

[0018] [Surface treatment liquid] A surface treatment liquid according to one embodiment of the present invention contains a resin compound (A) having a bisphenol skeleton represented by the following general formula (I), a cationic urethane resin emulsion (B) having at least one cationic functional group selected from primary to tertiary amino groups and a quaternary ammonium salt group, a silane coupling agent (C) having at least one reactive functional group selected from an active hydrogen-containing amino group, an epoxy group, a mercapto group and a methacryloxy group, an organic titanium chelate compound (D), a tetravalent vanadium compound (E), a phosphate compound (F), and water (G).

[0019] <Resin compound (A)> The resin compound (A) contained in the surface treatment liquid has a bisphenol skeleton represented by the following general formula (I): The resin compound (A) is a bisphenol-formalin condensate, and although there is no limitation on the synthesis method thereof, it can be obtained, for example, by reacting bisphenol A with formalin and an amine in the presence of an alkali catalyst. [ka]

[0020] In formula (I), Y1 and Y2 bonded to a benzene ring are each independently a hydrogen atom or a Z group represented by the following general formula (II) or (III), the average number of Z groups substituted per benzene ring is 0.2 to 1.0, and n represents an integer of 2 to 50. [ka] [ka]

[0021] In the present invention, by selecting Z groups as Y1 and Y2, the resin compound (A) has cationic functional groups of secondary and tertiary amino groups and quaternary ammonium bases, and therefore can be more stably dissolved in the acidic (pH 5.5 or less) surface treatment liquid targeted by the present invention.

[0022] In the present invention, the average value of the Z group substitution number is a value obtained by dividing the total number of Z groups introduced in Y1 and Y2 by the total number of benzene rings (i.e., 2n). If the average value of the Z group substitution number is less than 0.2, the resin compound cannot be stably dissolved in the surface treatment liquid. Therefore, the average value of the Z group substitution number is set to 0.2 or more. On the other hand, if the average value of the Z group substitution number exceeds 1.0, the corrosion resistance of the flat plate part and the processed part in SST decreases. Therefore, the average value of the Z group substitution number is set to 1.0 or less.

[0023] In the present invention, the average degree of polymerization n of the general formula (I) is 2 to 50. If n is less than 2, the corrosion resistance of the flat plate portion and the processed portion in SST becomes insufficient. Therefore, the average degree of polymerization n of the Z group is set to 2 or more. On the other hand, if n exceeds 50, the stability of the resin compound (A) in the surface treatment liquid decreases due to a decrease in the water solubility of the resin compound (A) and an increase in the viscosity of the surface treatment liquid, and the storage stability becomes insufficient. In addition, the corrosion resistance of the processed portion in SST becomes insufficient. Therefore, the average degree of polymerization n of the Z group is set to 50 or less.

[0024] In formula (II) and formula (III), R1, R2, R3, R4, and R5 each independently represent a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a hydroxyalkyl group having 1 to 10 carbon atoms. If the alkyl group or hydroxyalkyl group has more than 10 carbon atoms, the resin compound (A) cannot be sufficiently water-soluble, and becomes unstable in the surface treatment liquid. Therefore, the carbon numbers of R1, R2, R3, R4, and R5 are set to 10 or less. On the other hand, the carbon numbers of R1, R2, R3, R4, and R5 are set to 1 or more. Specific examples of R1, R2, R3, R4, and R5 include methyl, ethyl, propyl, butyl, hydroxyethyl, 2-hydroxypropyl, and hydroxyisobutyl.

[0025] In formula (III), A - represents a hydroxide ion or an acid ion. Specific examples of the acid ion include an acetate ion, a phosphate ion, and a formate ion.

[0026] <Cationic urethane resin emulsion (B)> The cationic urethane resin emulsion (B) in the surface treatment liquid of the present invention is not particularly limited in the polyol, isocyanate component, and polymerization method, which are the monomer components constituting the cationic urethane resin emulsion (B), as long as it has at least one cationic functional group selected from primary to tertiary amino groups and quaternary ammonium salt groups. Examples of the cationic functional group include amino groups, methylamino groups, ethylamino groups, dimethylamino groups, diethylamino groups, trimethylamino groups, and triethylamino groups, but there is no particular limitation as long as it is primary to tertiary amino groups or a quaternary ammonium salt group. On the other hand, nonionic urethane resin emulsions or anionic urethane resin emulsions cannot be used because they will coagulate during the preparation stage of the surface treatment liquid.

[0027] <Silane coupling agent (C)> The silane coupling agent (C) in the surface treatment liquid of the present invention is not particularly limited as long as it is a silane coupling agent having at least one reactive functional group selected from active hydrogen-containing amino group, epoxy group, mercapto group and methacryloxy group. In particular, a trialkoxysilane having three alkoxy groups is preferable. Specific examples include N-(2-aminoethyl)3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 2-(3,4 epoxycyclohexyl)ethyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, etc. If a silane coupling agent that does not have the above reactive functional group is used, the effect of improving the corrosion resistance of the processed part in SST cannot be obtained, and therefore it cannot be applied.

[0028] <Organic titanium chelate compound (D)> The organic titanium chelate compound (D) in the surface treatment solution of the present invention is not particularly limited, but examples thereof include titanium acetylacetonate, titanium octylene glycolate, titanium tetraacetylacetonate, and titanium ethylacetoacetate. Inorganic salts such as titanium nitrate, titanium sulfate, titanium acetate, titanium carbonate, and titanium hydrofluoric acid are not preferred because they cannot be stably dissolved in the surface treatment solution of the present invention or do not exhibit the effect of improving the corrosion resistance of the processed part in SST. When the organic titanium chelate compound is dissolved in water and used, titanium is dissolved as a chelate complex, so it is preferable not to add a highly polar water-soluble solvent or peroxide that affects this complex.

[0029] <Tetravalent vanadium compounds (E)> The tetravalent vanadium compound (E) in the surface treatment solution of the present invention is not particularly limited, but examples thereof include vanadyl sulfate, vanadyl dichloride, vanadyl phosphate, vanadyl oxalate, vanadyl acetylacetonate, etc. Pentavalent vanadium compounds are not used in the present invention because they are highly water-soluble and therefore highly elutable from the surface treatment film, have little effect on improving the corrosion resistance of the processed part in SST, and have low storage stability of the surface treatment solution. In addition, the tetravalent vanadium compound used in the surface treatment solution of the present invention is VO 2+ Vanadium compounds that generate (vanadyl) ions are most preferred because they are highly effective in improving the corrosion resistance of processed parts during SST.

[0030] <Phosphate Compounds (F)> The phosphoric acid compound (F) in the surface treatment liquid of the present invention is not particularly limited, and examples thereof include acids and salts thereof such as phosphoric acid, phosphonic acid, polyphosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, triammonium phosphate, aluminum phosphate, manganese phosphate, magnesium phosphate, calcium phosphate, etc. In the present invention, it is preferable to use one or more selected from these.

[0031] [(B S ) / {(A S )+(B S )+(C S)} is 0.10 or more] In the surface treatment liquid of the present invention, the solid content by mass of the resin compound (A) S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S ) the solid content mass (B S ) ratio [(B S ) / {(A S )+(B S )+(C S If the mass ratio is less than 0.10, the proportion of urethane resin is too small, resulting in insufficient corrosion resistance and sweat resistance of the processed part in the SST. S ) / {(A S )+(B S )+(C S )}] is 0.10 or more, and preferably 0.12 or more. On the other hand, although there is no particular upper limit to the mass ratio, if the mass ratio exceeds 0.30, the solvent resistance is poor, so that the mass ratio is preferably 0.30 or less, and more preferably 0.28 or less.

[0032] [(C S ) / {(A S )+(B S )+(C S )} is 0.85 or less] In the surface treatment liquid of the present invention, the solid content by mass of the resin compound (A) S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S ) based on the total solid content (C S ) ratio [(C S ) / {(A S )+(B S )+(C S It is necessary to set the mass ratio [(C )}] to 0.85 or less. If the mass ratio exceeds 0.85, the corrosion resistance and sweat resistance of the processed part in SST become insufficient. Therefore, it is necessary to set the mass ratio [(C S ) / {(AS )+(B S )+(C S )}] is 0.85 or less, and preferably 0.80 or less. On the other hand, if the mass ratio is less than 0.60, the solvent resistance is poor, so the mass ratio is preferably 0.60 or more, and more preferably 0.65 or more.

[0033] [{(C S ) / (D Ti )} is between 50 and 70 In the surface treatment solution of the present invention, the titanium-equivalent mass of the organic titanium chelate compound (D) is Ti ) the solid content mass of the silane coupling agent (C) (C S ) ratio {(C S ) / (D Ti It is important that the mass ratio is 50 or more and 70 or less. If the mass ratio is less than 50, the corrosion resistance of the processed part in the SST and the storage stability of the surface treatment solution are poor. S ) / (D Ti )} is set to be 50 or more. On the other hand, if the mass ratio exceeds 70, the elution of the surface treatment film increases, and the corrosion resistance of the flat plate and processed parts in the SST decreases. S ) / (D Ti )} is 70 or less, and preferably 65 or less.

[0034] In calculating the various mass ratios in the surface treatment solution of the present invention, the solid mass of the silane coupling agent (C S ) is the mass of alkoxysilane (R-Si(-OR1)3) hydrolyzed into silanol (RSi(-OH)3). This is because when a silane coupling agent is dissolved in water, most of it is hydrolyzed, and the alcohol generated by hydrolysis volatilizes when the surface treatment liquid of the present invention is applied and dried to form a surface treatment film, and does not act as an active ingredient.

[0035] [{(E V ) / (D Ti )} is 0.30 or more] In the surface treatment solution of the present invention, the titanium-equivalent mass of the organic titanium chelate compound (D) is Ti ) to the vanadium-equivalent mass (E V ) ratio {(E V ) / (D Ti )} is 0.30 or more. If the mass ratio is less than 0.30, the corrosion resistance of the processed part in SST is poor. Therefore, {(E V ) / (D Ti )} is 0.30 or more, and preferably 0.35 or more. On the other hand, if the mass ratio exceeds 0.50, the paintability after alkaline degreasing decreases, so {(E V ) / (D Ti )} is preferably 0.50 or less, and more preferably 0.48 or less.

[0036] [{(F P ) / (T S )} is 0.015 or more and 0.400 or less] In the surface treatment solution of the present invention, the total solid content (T S ) to the phosphorus equivalent mass (F P ) ratio {(F P ) / (T s )} is 0.015 or more and 0.400 or less. If the mass ratio is less than 0.015, the corrosion resistance and sweat resistance in an environment where salt accumulates are poor. Therefore, {(F P ) / (T s )} is 0.015 or more, preferably 0.030 or more, and more preferably 0.050 or more. P ) / (T s If {(F P ) / (T s )} is set to 0.400 or less, preferably 0.300 or less, and more preferably 0.200 or less.

[0037] The pH of the surface treatment solution of the present invention is 5.5 or less. If the pH of the surface treatment solution exceeds 5.5, the storage stability of the surface treatment solution cannot be obtained. As a result, the surface treatment film formed tends to be non-uniform, and the corrosion resistance in an environment where SST and salt accumulate tends to deteriorate. On the other hand, the lower limit of the pH of the surface treatment solution is not particularly limited, but it is preferably about 3 or more.

[0038] Here, as the acidic agent used to adjust the pH to 5.5 or less, acetic acid, formic acid, hydrofluoric acid, fluorides, etc. are preferred, and strong acids such as sulfuric acid and nitric acid are not preferred. When sulfuric acid or nitric acid is used, the cationic phenolic resin or cationic urethane resin emulsion tends to become a gel-like substance in the surface treatment solution due to a pH shock (local and sudden pH change) during pH adjustment. Acetic acid and formic acid are weak acids and are suitable for pH adjustment. Furthermore, these weak acids are highly volatile and volatilize when the surface treatment solution of the present invention is dried, leaving little residue in the surface treatment film, so they are also preferred in that there is little performance degradation even if they are added in excess. In addition, the phosphoric acid compound (F) contained in the surface treatment solution reacts with the surface of the zinc-based plated steel sheet to form a protective film that is sparingly soluble and has high barrier properties, so that the corrosion resistance in SST does not deteriorate even if the pH of the surface treatment solution is low.

[0039] <Water (G)> The water (G) contained in the surface treatment liquid of the present invention is preferably one that has little effect on the resin compound (A), cationic urethane resin emulsion (B), silane coupling agent (C), and organic titanium chelate compound (D), as well as on the acid or alkali component used for adjusting the pH. For example, hardness-increasing components such as Mg, Ca, and Si contained as impurities in water are undesirable because they reduce the solubility and dispersibility of the resin compound (A) and cationic urethane resin emulsion (B) of the present invention and can cause the generation of aggregates of these.

[0040] Furthermore, impurities such as Na and Cl contained in water may reduce the SST corrosion resistance and paint adhesion if they remain in the surface treatment film. Therefore, it is preferable that the water (G) contains few impurities, and for example, its electrical conductivity is preferably less than 100 μS / cm. More preferably, it is 50 μS / cm or less, and even more preferably, it is 10 μS / cm or less.

[0041] The solid content of the surface treatment solution in the present invention is preferably 4 to 20% by mass as determined by drying for 2 hours at 110° C. By setting the solid content within the range of 4 to 20% by mass, it becomes easy to ensure the adhesion amount of the surface treatment film described below, and excellent storage stability can be obtained.

[0042] The basic components of the surface treatment solution of the present invention have been described above. The surface treatment solution of the present invention may consist of the above components, and may further contain the following components as necessary.

[0043] In the present invention, the surface treatment solution may contain a molybdic acid compound (H) for the purpose of ensuring resistance to blackening caused by the surface treatment film. The type of molybdic acid compound (H) used in the surface treatment solution in the present invention is not particularly limited, but specific examples include molybdic acid, ammonium molybdate, sodium molybdate, potassium molybdate, magnesium molybdate, zinc molybdate, etc., and also phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, etc. In the present invention, it is preferable to use one or more types selected from these.

[0044] In the surface treatment liquid of the present invention, the solid content by mass of the resin compound (A) S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S ) of molybdenum-equivalent mass (H Mo ) ratio [(H Mo ) / {(AS )+(B S )+(C S )}] is preferably 0.003 to 0.03. If the mass ratio is less than 0.003, the resistance to blackening is poor, and if it exceeds 0.03, the storage stability of the surface treatment liquid cannot be obtained. In order to obtain a higher level of resistance to blackening, it is more preferably 0.006 or more.

[0045] In the present invention, the surface treatment solution may contain a fluorine compound (I) for the purpose of improving the sweat resistance of the surface treatment film. The type of fluorine compound (I) used in the surface treatment solution in the present invention is not particularly limited, but specific examples include acids such as hydrofluoric acid, hydrofluorosilicic acid, hydroboric acid, hydrofluoric titanic acid, and hydrofluoric zirconic acid, and salts thereof. In the present invention, it is preferable to use one or more selected from these.

[0046] In the surface treatment liquid of the present invention, the solid content by mass of the resin compound (A) S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S ) the fluorine-equivalent mass (I F ) ratio [(I F ) / {(A S )+(B S )+(C S )}] is preferably 0.01 to 0.1. If the mass ratio is less than 0.01, the effect of adding the fluorine compound (I) cannot be obtained. On the other hand, if the mass ratio exceeds 0.1, the corrosion resistance of the flat plate in the SST and the storage stability of the surface treatment solution cannot be obtained.

[0047] Furthermore, in the present invention, the surface treatment liquid may contain wax (W) for the purpose of ensuring the lubricity of the surface treatment film. S ) and the solid content mass of the cationic urethane resin emulsion (B) (B SThe ratio of the solid mass (Ws) of the wax (W) to the total mass (A S )+(B S It is preferable that the mass ratio is 0.2 to 0.4. By making the mass ratio 0.2 or more, the desired lubricity can be obtained. Therefore, [(Ws) / {(A S )+(B S )}] is preferably 0.2 or more, more preferably 0.3 or more. On the other hand, by setting the mass ratio to 0.4 or less, lubricity can be ensured, it is economically advantageous, and furthermore, it is preferable since it does not deteriorate the corrosion resistance of the flat plate part and the processed part in SST, and furthermore, the corrosion resistance in an environment where salt accumulates.

[0048] The wax (W) used in the present invention is preferably at least one selected from those having a melting point of 70 to 120° C., specific examples of which include polyethylene wax, oxidized polyethylene wax, polypropylene wax, microcrystalline wax, etc. A melting point of 70° C. or higher provides the desired lubricity, while a melting point of 120° C. or lower provides a coating that is not too hard and at the same time provides the desired lubricity.

[0049] The wax (W) is preferably an emulsion stably dispersed in water with an emulsifier, and preferably has a particle size of 0.08 to 0.3 μm. By setting the particle size to 0.08 μm or more, the desired lubrication effect can be obtained, and the amount of emulsifier used is not increased, so that the alkali resistance and paintability are not reduced, which is preferable. On the other hand, by setting the particle size to 0.3 μm or less, the specific gravity of the wax (W) is lowered, so that floating and separation in the surface treatment liquid does not occur, and storage stability is excellent, which is preferable.

[0050] The surface treatment solution of the present invention may contain an antifoaming agent, a wettability improver, etc., if necessary. The type of antifoaming agent is not particularly limited, and for example, a silicone-based or fatty acid-based emulsion type can be used. The wettability improver reduces the surface tension of the surface treatment solution, improves the wettability of the surface of the zinc-based plated steel sheet, and improves the uniformity of the appearance. Examples of the wettability improver include water-soluble solvents such as ethanol, tert-butanol, and butyl cellosolve, but are not limited to these. In addition, wettability improvers containing acetylene are suitable because they also have an antifoaming effect. Nitrates such as nickel nitrate and ammonium nitrate may be added to the surface treatment solution of the present invention in order to further improve the blackening resistance. As described above, nitric acid causes a pH shock, but nitrates do not cause a pH shock.

[0051] [Method of manufacturing zinc-based coated steel sheet with surface treatment film] Next, a method for producing a zinc-based plated steel sheet with a surface treatment film according to one embodiment of the present invention will be described. In the method for producing a zinc-based plated steel sheet with a surface treatment film according to one embodiment of the present invention, the above-mentioned surface treatment liquid is applied to the surface of a zinc-based plated steel sheet, which is then dried under conditions where the maximum sheet temperature is 40 to 180°C, so that the coating weight per side is 0.2 g / m 2 The method includes the step of forming the surface treatment film described above.

[0052] The amount of coating applied on one side of the surface treatment film is 0.2 g / m 2 If the coating weight is less than 0.2 g / m, sufficient corrosion resistance of flat plate parts and processed parts in SST, and furthermore corrosion resistance in an environment where salt accumulates, cannot be obtained. Therefore, the coating weight per side is 0.2 g / m 2 More than 0.3 g / m 2 It is preferable that the density is 0.5 g / m or more. 2 On the other hand, it is more preferable that the coating weight per one side of the surface treatment film is 1.8 g / m or more. 2 Above this amount, the effect of the coating mass becomes saturated, which is economically disadvantageous, and processing can easily cause peeling between the surface treatment film and the zinc-based plated steel sheet surface, which can reduce the corrosion resistance of the processed area during SST. Therefore, the coating mass per side should be 1.8 g / m2 It is preferable that the density is 1.3 g / m or less. 2 More preferably, it is 1.0 g / m or less. 2 It is more preferable that:

[0053] The method for applying the surface treatment solution of the present invention to the surface of a zinc-based plated steel sheet may be any of a coating method, a dipping method, and a spraying method. The coating method may be any of the conventionally known methods such as a roll coater (three-roll method, two-roll method, etc.), a squeeze coater, a die coater, a bar coater, etc. After the surface treatment solution is applied, it is also possible to adjust the amount of coating, uniform the appearance, and uniform the film thickness by an air knife method, a roll squeezing method, etc.

[0054] After the surface treatment solution of the present invention is coated (applied) on the surface of the zinc-plated steel sheet, it is preferably dried by heating without washing with water. As the drying means, a dryer, a hot air oven, a high-frequency induction heating oven, an infrared oven, etc. can be used. Drying is performed so that the maximum temperature reached on the surface of the zinc-plated steel sheet (drying temperature) is in the range of 40 to 180°C. If the drying temperature is lower than 40°C, a large amount of moisture remains in the surface treatment film, and the properties of the surface treatment film are not stable. On the other hand, if the drying temperature exceeds 180°C, it is uneconomical, and the surface treatment film becomes hard and brittle, and the corrosion resistance of the processed part in SST is reduced. Furthermore, if the drying temperature exceeds 180°C, the reaction of the phosphate compound (F) contained in the surface treatment film proceeds in the surface treatment film, and as a result, the solubility of the phosphate compound (F) in a wet environment is reduced, and the corrosion resistance in an environment where salt accumulates is reduced.

[0055] The zinc-based plated steel sheet with a surface treatment film formed by the above-mentioned manufacturing method can be further coated with a resin film on its surface to obtain a higher level of corrosion resistance. The surface treatment film formed by the surface treatment solution of the present invention may be applied to either one or both sides of the zinc-based plated steel sheet.

[0056] Next, the action of the present invention will be described. It is assumed that each component in the surface treatment solution of the present invention has the following action, but the present invention is not limited to these assumptions.

[0057] The surface treatment liquid of the present invention mainly comprises a resin compound (A), a cationic urethane resin emulsion (B), and a silane coupling agent (C), and these main components form the skeleton of the surface treatment film.

[0058] By adjusting the pH of the surface treatment solution containing the resin compound (A) having a cationic functional group to a weak acidity, the stability of the surface treatment solution is increased and storage stability is ensured. Furthermore, by imparting cationicity, the resin compound (A) becomes insoluble in an alkaline solution, resulting in an alkali-resistant surface treatment film. By having an alkali-resistant surface treatment film, corrosion resistance can be exhibited even if an alkaline site is formed in a corrosive environment. In other words, SST corrosion resistance and corrosion resistance in an environment where salt is deposited can be imparted. Furthermore, by selecting bisphenol as the phenol skeleton of the resin compound (A), it becomes difficult to dissolve in polar solvents (imparting solvent resistance). Furthermore, as a result of improving adhesion, the corrosion resistance of the flat plate part and the processed part in SST is also improved.

[0059] However, the resin compound (A) tends to increase the hardness of the surface treatment film, which tends to reduce the adhesion between the surface treatment film and the surface of the zinc-plated steel sheet. Therefore, in the present invention, the cationic urethane resin emulsion (B) is blended to reduce the hardness of the phenolic resin and improve the adhesion between the surface treatment film and the surface of the zinc-plated steel sheet, thereby ensuring the corrosion resistance of the flat plate part and the processed part in the SST.

[0060] In the present invention, a silane coupling agent (C) is blended for the purpose of improving the adhesion between the surface treatment film and the surface of a zinc-plated steel sheet, improving the corrosion resistance of the flat and processed parts in SST, and further improving the corrosion resistance in an environment where salt accumulates. The silane coupling agent (C) contributes to improving the adhesion to the surface of a zinc-plated steel sheet because the terminal alkoxy group is hydrolyzed to generate an active silanol group (Si-OH). Furthermore, a part of the silane coupling agent (C) is dehydrated and condensed to generate a siloxane bond (Si-O-Si), which is continuously polymerized (polysiloxane formation: -Si-O-Si-O-Si-). This results in an extremely stable structure, which can impart the corrosion resistance of the flat and processed parts in SST, and furthermore, solvent resistance, to the surface treatment film.

[0061] In addition to the above main components, the surface treatment solution of the present invention contains an organic titanium chelate compound (D) as an essential component. It is presumed that the organic titanium chelate compound (D) acts as a catalyst to promote polysiloxane formation when the surface treatment solution is dried to form a surface treatment film. This improves the corrosion resistance and solvent resistance of the flat plate and processed parts in the SST.

[0062] In order to obtain the above-mentioned effect, as mentioned above, a certain amount of organic titanium chelate compound (D) is required, which is determined according to the amount of silane coupling agent (C). If the amount is small, the desired effect cannot be obtained, and if the amount is excessive, the polysiloxane increases too much, resulting in a hard and brittle film, and the corrosion resistance of the processed part in SST decreases. In addition, although it is ideal that polysiloxane formation by organic titanium chelate compound (D) is promoted during film formation, polysiloxane formation is also promoted during storage of the surface treatment liquid, so if the content is excessive, storage stability (suppression of thickening and gelation) decreases, and the same quality as before storage cannot be obtained after storage.

[0063] The surface treatment solution of the present invention also requires a tetravalent vanadium compound (E) as an essential component. In the present invention, the tetravalent vanadium compound (E) is presumed to act as a corrosion inhibitor (e.g., zinc passivation). In particular, the vanadyl ion having one oxygen atom [VO 2+)] is unlikely to dissolve even in a humid environment and remains in the film while exerting its inhibitor effect, so that even if the zinc-based plated steel sheet is subjected to strong processing such as bending, and the surface treatment film or zinc-based plated surface itself suffers from ductile damage, the corrosion resistance of that part in SST is improved. Note that the inventors speculate that this effect is achieved by a synergistic effect with Ti, which also exists as a cation, on the premise that the skeleton of the surface treatment film having cationic functional groups is appropriate.

[0064] Furthermore, it is important that the surface treatment solution of the present invention contains a phosphoric acid compound (F) as an essential component. Unlike the SST environment, an environment where salt accumulates, such as under the eaves, contains a large amount of Cl, which is a corrosion factor. - In addition, the surface treatment film is easily destroyed by the repeated drying and wetting during the day and night. Therefore, the inventors speculated that simply imparting barrier properties to the surface treatment film in order to ensure corrosion resistance in SST would not provide sufficient corrosion resistance in an environment where salt accumulates.

[0065] Therefore, the inventors have studied a method for suppressing corrosion in the area where the surface treatment film is destroyed by repeated drying and wetting. As a result, they have found that corrosion in an environment where salt accumulates can be suppressed by including a phosphate compound in the surface treatment film. The mechanism of corrosion suppression is presumed to be as follows. The surface treatment film is partially destroyed by repeated drying and wetting, exposing the surface of the zinc-based plated steel sheet. However, the phosphate compound contained in the surface treatment film dissolves into the water film formed in the corrosive environment, and the zinc-based plated steel sheet surface reacts with the phosphate compound to form a protective film that is sparingly soluble and has a high barrier property. As a result, corrosion resistance can be achieved in an environment where salt accumulates. In an environment where salt accumulates, the phosphate compound is not washed away because there is no washing effect by salt water, and it remains in the film, contributing to the improvement of corrosion resistance.

[0066] On the other hand, if the surface treatment film contains an excessive amount of phosphate compounds, the barrier properties of the surface treatment film are reduced, resulting in insufficient corrosion resistance in SST. This is thought to be because SST is an environment where salt water is constantly supplied, and the corrosion inhibition mechanism that is established in an environment where salt accumulates does not work.

[0067] Furthermore, the phosphate compound (F) can improve sweat resistance. When a person touches a zinc-based plated steel sheet directly, the person's sweat adheres to the surface of the zinc-based plated steel sheet, and this part discolors over time. The mechanism of this discoloration phenomenon is not yet clear, but it is believed that the very surface of the zinc-based plating is gradually oxidized by human sweat (weak acidity), which is the cause of the discoloration. The phosphate compound is believed to have the following effects on sweat resistance. The phosphate compound contained in the surface treatment film has the effect of gradually oxidizing the surface layer of the zinc-based plating in a natural environment. Therefore, since oxidation gradually progresses even in the peripheral area of ​​the sweat-adhered area, even if discoloration due to oxidation occurs in the sweat-adhered area, no color difference is caused between the sweat-adhered area and the peripheral area, and it is possible to prevent the appearance from becoming uneven. In Patent Document 1 and the like, sweat resistance is improved by adding a fluorine compound, but the fact that sweat resistance can be improved by a phosphate compound is a new finding in the present invention.

[0068] Furthermore, the surface treatment solution of the present invention may contain molybdenum oxide (H) for the purpose of imparting excellent blackening resistance. Blackening of zinc-based plating occurs regardless of the type of plating (electrical or hot-dip), and in particular, Mg or Al is added to hot-dip zinc-based plating to improve corrosion resistance or adhesion between the zinc plating and the underlying steel sheet, and these are concentrated at the plating interface or surface layer of the zinc-based plating, promoting blackening and making it darker. It is also known that surface treatment to improve the white rust resistance of zinc-based plating reduces blackening resistance.

[0069] As mentioned above, the cause of the phenomenon in which zinc-based plating turns black under high-temperature and high-humidity conditions is still unclear, but it is said that the zinc oxide formed on the outermost surface of the zinc-based plating loses oxygen and transforms into oxygen-deficient zinc oxide, or that oxygen-deficient zinc oxide is formed due to insufficient oxygen being supplied during the zinc corrosion (oxidation) process, which causes it to appear black.

[0070] In the present invention, a compound of molybdic acid may be introduced into the surface treatment film for the purpose of imparting excellent blackening resistance. Molybdenum is a transition metal, and exists as an oxide of MoO2 or MoO3 when combined with oxygen. Furthermore, molybdic acid (MoO4 2- Therefore, in the present invention, molybdic acid (MoO4 2- It is believed that when a portion of the zinc oxide is converted to molybdenum oxide (MoO3, etc.) under high temperature and humidity or in a corrosive environment, an appropriate amount of oxygen is supplied to the zinc-based plating surface, making it difficult for oxygen-deficient zinc oxide to form. The inventors speculate that this mechanism allows the formation of a surface treatment film that suppresses blackening.

[0071] Regarding steps and conditions not described in the present invention, conventional methods can be used. EXAMPLES

[0072] Prepared were resin compounds (A) shown in Table 1 (Tables 1A and 1B), urethane resin emulsions (B) shown in Table 2, silane coupling agents (C) shown in Table 3, titanium compounds (D) shown in Table 4, vanadium compounds (E) shown in Table 5, and phosphate compounds (F) shown in Table 6. In addition, various zinc-based plated steel sheets shown in Table 7 were used as the zinc-based plated steel sheets.

[0073] The components shown in Tables 1 to 6 were mixed in the blending ratios shown in Tables 8-1 and 8-2, and the pH was adjusted with acetic acid or ammonia to the value shown in Table 8-2. Deionized water was then added so that the solids concentration after drying for 2 hours at 110° C. was 10% by mass, to prepare surface treatment solutions of various levels. Note that ion-exchanged water with an electrical conductivity of 10 μS / cm was used as the deionized water.

[0074] A surface treatment solution was applied to one side of a zinc-based plated steel sheet of the type shown in Table 8-3 using a roll coater, and the sheet was heated and dried under the drying conditions shown in Table 8-3 without rinsing with water to produce a zinc-based plated steel sheet with a surface treatment film. The adhesion amount of the surface treatment film per side was adjusted to the adhesion amount shown in Table 8-3 by adjusting the application conditions (roll pressure, rotation speed, etc.).

[0075] The amount of the surface treatment film attached was determined by quantifying the amount of Si in the blended silane coupling agent (C) using a fluorescent X-ray analyzer and converting it into the amount of Si attached.

[0076] The properties of the zinc-based plated steel sheets (samples) with surface treatment films were evaluated (corrosion resistance of flat plate parts in SST, corrosion resistance of processed parts in SST, corrosion resistance in salt-accumulating environments, sweat resistance) and the storage stability of the surface treatment solution was evaluated. The results are shown in Table 9. Each evaluation was performed under the following conditions.

[0077] (1) Corrosion resistance of flat surfaces in SST Each sample was subjected to a salt spray test (JIS-Z-2371-2000) and evaluated based on the area ratio of white rust after 120 hours. The evaluation criteria are as follows: ◎: White rust occurrence area rate 0% ○+: White rust occurrence area rate is over 0% and less than 5% ○: White rust occurrence area rate is 5% or more, but less than 10% ○-: White rust occurrence area rate is 10% or more, less than 20% △: White rust occurrence area rate is 20% or more, but less than 40% ×: White rust occurrence area rate is 40% or more

[0078] (2) Corrosion resistance of processed parts in SST Each sample was bent 180 degrees so as to be sandwiched between a rod (made of stainless steel) with a diameter of 2 mm, and then clamped using a vice. The bent samples were subjected to a salt spray test (JIS-Z-2371-2000), and evaluated based on the area ratio of white rust on the outside (front) side of the bent part after 72 hours. The evaluation criteria are as follows: ◎: 0% of the area has white rust on the bent part ○+: White rust occurrence area rate of bent part is over 0% and less than 5% ○: White rust occurrence area rate of bent part is 5% or more, less than 10% ○-: White rust occurrence area rate of bent parts is 10% or more, less than 40% △: White rust occurrence area rate of bent part is 40% or more, but less than 80% ×: White rust occurrence area rate of bent part is 80% or more

[0079] (3) Corrosion resistance of flat plates in salt-accumulating environments Each sample underwent a salt adhesion cycle test (JIS G0594:2019 (Method D), test liquid: 10-fold diluted liquid) for 12 weeks (84 days) and was evaluated by corrosion weight loss (ISO8407). Here, the cleaning process was omitted in order to simulate an environment in which salt accumulates. The evaluation criteria are as follows: ◎: Corrosion weight loss 5g / m 2 less than ○: Corrosion weight loss 5g / m 2 More than 10g / m 2 less than △: Corrosion weight loss 10g / m 2 More than 15g / m 2 less than ×: Corrosion weight loss 15g / m 2 End

[0080] (4) Storage stability of surface treatment solution Each surface treatment solution was stored in a thermostatic chamber at 40° C. for 30 days. After removal, the appearance of each surface treatment solution was visually inspected and evaluated. The evaluation criteria were as follows: ◎: No change ○: A very small amount of precipitation is observed △: A small amount of precipitation was observed or the viscosity became slightly high. ×: A large amount of precipitation was observed or gelation occurred.

[0081] (5) Sweat resistance 10μL of artificial sweat conforming to JIS B7001-1995 was dropped onto the surface of each sample, and a silicone rubber stopper was pressed onto the drop to prepare a test piece contaminated with artificial sweat of a certain area. The test piece was left to stand for 4 hours in a thermo-hygrostat controlled at a temperature of 40℃ and a relative humidity of 80%, after which the appearance change of the area contaminated with artificial sweat was evaluated. The evaluation criteria are as follows: ◎: Areas contaminated with artificial sweat are not noticeable ○: Areas contaminated with artificial sweat are slightly discernible △: Areas contaminated with artificial sweat can be identified ×: Areas contaminated with artificial sweat are clearly identifiable

[0082] [Table 1A]

[0083] [Table 1B]

[0084] [Table 2]

[0085] [Table 3]

[0086] [Table 4]

[0087] [Table 5]

[0088] [Table 6]

[0089] [Table 7]

[0090] [Table 8-1] TIFF2025040894000016.tif242170

[0091] [Table 8-2] TIFF2025040894000018.tif248118

[0092] [Table 8-3] TIFF2025040894000020.tif248129

[0093] [Table 9] TIFF2025040894000022.tif248122

[0094] As shown in Table 9, the examples of the present invention are excellent in all aspects: flat plate corrosion resistance under SST, processed plate corrosion resistance under SST, flat plate corrosion resistance in an environment where salt accumulates, storage stability, and sweat resistance. [Industrial Applicability]

[0095] A zinc-based plated steel sheet having a surface treatment film produced using the surface treatment solution of the present invention can be widely used in the fields of automobiles, home appliances, building materials, etc.

Claims

1. A resin compound (A) having a bisphenol skeleton represented by the following general formula (I), a cationic urethane resin emulsion (B) having at least one cationic functional group selected from primary to tertiary amino groups and a quaternary ammonium salt group; a silane coupling agent (C) having at least one reactive functional group selected from an active hydrogen-containing amino group, an epoxy group, a mercapto group, and a methacryloxy group; An organic titanium chelate compound (D); A tetravalent vanadium compound (E); A phosphoric acid compound (F), Water (G) in an amount satisfying the following conditions (1) to (5) and having a pH of 5.5 or less. (1) The solid content mass (A S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S The solid content mass (B) of the cationic urethane resin emulsion (B) relative to the total S ) ratio [(B S ) / {(A S ) + (B S ) + (C S )) is 0.10 or more (2) The solid content mass (A S ), the solid content mass of the cationic urethane resin emulsion (B) (B S ), and the solid content mass of the silane coupling agent (C) (C S The solid content mass (C S ) ratio [(C S ) / {(A S ) + (B S ) + (C S ) ) ] is 0.85 or less (3) The titanium-equivalent mass (D) of the organic titanium chelate compound (D) Ti ) the solid content mass (C S ) ratio {(C S ) / (D Ti )) is between 50 and 70 (4) The titanium-equivalent mass (D) of the organic titanium chelate compound (D) Ti The vanadium-equivalent mass (E) of the tetravalent vanadium compound (E) relative to V ) ratio {(E V ) / (D Ti ) is 0.30 or more (5) The total solid mass of the surface treatment solution (T S ) relative to the phosphorus equivalent mass (F) of the phosphoric acid compound (F) P ) ratio {(F P ) / (T s )) is 0.015 to 0.400 【Chemistry 1】 In formula (I), Y bonded to a benzene ring 1 and Y 2 are each independently a hydrogen atom or a Z group represented by the following general formula (II) or (III), the average number of Z groups substituted per benzene ring is 0.2 to 1.0, and n represents an integer of 2 to 50. 【Chemistry 2】 【Chemistry 3】 In formulas (II) and (III), R 1 , R 2 , R 3 , R 4 and R 5 are each independently a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a hydroxyalkyl group having 1 to 10 carbon atoms; A - represents a hydroxide ion or an acid ion.

2. The surface treatment solution according to claim 1 is applied to the surface of a zinc-based plated steel sheet, and then dried under conditions of a maximum sheet temperature of 40 to 180°C, so that the coating weight per one side is 0.2 g / m 2 A method for producing a zinc-based plated steel sheet having a surface treatment film, comprising the above-described step of forming a surface treatment film.

3. A zinc-based plated steel sheet having a surface treatment film, produced by the method for producing a zinc-based plated steel sheet having a surface treatment film according to claim 2.

Citation Information

Patent Citations

  • Surface-treating liquid for zinc-plated steel sheet, and zinc-plated steel sheet and method for manufacturing the same

    JP2011179057A

  • Surface treatment fluid for zinc-plated steel sheet, zinc-plated steel sheet, and method for manufacturing the same

    JP2012067369A

  • Hot-dip galvanized steel sheet and method for manufacturing the same

    JP2012072476A

  • Method for producing galvanized steel sheet and galvanized steel sheet

    JP2012092444A

  • Chromate-free precoated metal sheet and substrate treatment agent for precoated metal sheet

    JP2012237065A